The physiology of lipid storage and use in reptiles. (27th June 2016) - Price, Edwin R.
ABSTRACT: Lipid metabolism is central to understanding whole‐animal energetics. Reptiles store most excess energy in lipid form, mobilise those lipids when needed to meet energetic demands, and invest lipids in eggs to provide the primary source of energy to developing embryos. Here, I review the mechanisms by which non‐avian reptiles store, transport, and use lipids. Many aspects of lipid absorption, transport, and storage appear to be similar to birds, including the hepatic synthesis of lipids from glucose substrates, the transport of triglycerides in lipoproteins, and the storage of lipids in adipose tissue, although adipose tissue in non‐avian reptiles is usually concentrated in abdominal fat bodies or the tail. Seasonal changes in fat stores suggest that lipid storage is primarily for reproduction in most species, rather than for maintenance during aphagic periods. The effects of fasting on plasma lipid metabolites can differ from mammals and birds due to the ability of non‐avian reptiles to reduce their metabolism drastically during extended fasts. The effect of fasting on levels of plasma ketones is species specific: β‐hydroxybutyrate concentration may rise or fall during fasting. I also describe the process by which the bulk of lipids are deposited into oocytes during vitellogenesis. Although this process is sometimes ascribed to vitellogenin‐based transport in reptiles, the majority of lipid deposition occurs via triglycerides packaged in very‐low‐density lipoproteins (VLDLs), based on physiological, histological, biochemical, comparative, and genomic evidence. I also discuss the evidence for non‐avian reptiles using 'yolk‐targeted' VLDLs during vitellogenesis. The major physiological states – feeding, fasting, and vitellogenesis – have different effects on plasma lipid metabolites, and I discuss the possibilities and potential problems of using plasma metabolites to diagnose feeding condition in non‐avian reptiles.